Sosyal Bilimlerde Güncel Araştırma ve İncelemeler V - Özgür, Ömer Faruk; Selvan, Esra; Koç, Okan; Dora, Metin; Yapıcıoğlu Ayaz, Yeliz; Çetin, Hüsamettin; Arslan, Kübra; Yaşa, Rıfat; Kantar, Hatice; Çomu, Aslı Emine; Külcü, Recep; Coşkun, Nazan; et al. (Academician Publishing Book DOI Portal, 2023)
-